2019
DOI: 10.1177/0363546518819217
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport and Reoperation Rates in Patients Under the Age of 20 After Primary Anterior Cruciate Ligament Reconstruction: Risk Profile Comparing 3 Patient Groups Predicated Upon Skeletal Age

Abstract: Background: With sports specialization and level of competition on the rise, anterior cruciate ligament reconstruction (ACLR) in athletes under the age of 20 has increased significantly in recent years. Reports have demonstrated that the revision ACLR rate is higher and return to sport (RTS) rate is lower in this population. Purpose: To evaluate the 2-year clinical outcomes of 3 cohorts of primary ACLR in pediatric and adolescent athletes under the age of 20 based on skeletal age with a focus on RTS and the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
74
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 44 publications
6
74
5
Order By: Relevance
“…5,7,17,21,23,46 Thus, the revision rate of 14% would compare favorably with the rate noted for suture repair without a scaffold in this patient population 13 and may be similar to that reported for autograft ACLR for this group. 5,7,17,21,23,46 Also interesting was that patients in the BEAR group who had a revision ACLR had a mean IKDC Subjective Score at 2 years similar to that of patients who had only a primary ACLR (85.5 vs 84.8 points) and that the AP knee laxity values were also similar (1.4 vs 1.8 mm). This is in contrast to previous reports of revision ACL surgery of a primary ACLR, which indicated poorer IKDC Subjective Scores (8-point difference at 2 years) 54 than those of patients who did not have that second procedure.…”
Section: Discussionsupporting
confidence: 74%
“…5,7,17,21,23,46 Thus, the revision rate of 14% would compare favorably with the rate noted for suture repair without a scaffold in this patient population 13 and may be similar to that reported for autograft ACLR for this group. 5,7,17,21,23,46 Also interesting was that patients in the BEAR group who had a revision ACLR had a mean IKDC Subjective Score at 2 years similar to that of patients who had only a primary ACLR (85.5 vs 84.8 points) and that the AP knee laxity values were also similar (1.4 vs 1.8 mm). This is in contrast to previous reports of revision ACL surgery of a primary ACLR, which indicated poorer IKDC Subjective Scores (8-point difference at 2 years) 54 than those of patients who did not have that second procedure.…”
Section: Discussionsupporting
confidence: 74%
“…The rate of revision ACLR was significantly greater (20%) in the partial transphyseal/complete transphyseal with hamstring autograft group compared with the allepiphyseal technique with HT autograft and BPTB groups (both 6%). 15 These results highlight a group of 8th-and 9th-grade adolescents who are at high risk for graft rupture. There are several potential explanations for this greater rate of revision, including surgical technique, graft choice, level of competition, and the physical and sports-specific development of the athlete.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, Cordasco et al 15 reported the 2-year return to sport and reoperation rates in 324 athletes younger than 20 years of age who underwent ACLR. Surgical technique was based on skeletal age and included an all-epiphyseal technique with hamstring autograft, MODIFIED LEMAIRE TENODESIS WITH PEDIATRIC ACL e113 partial transphyseal and complete transphyseal with hamstring autograft, and BPTB autograft.…”
Section: Discussionmentioning
confidence: 99%
“… 3 However, incidence of graft failure is still high, with reported rates of retear ranging anywhere from 6% to 38%, largely dependent on the age and level of competition within the pediatric and young adolescent cohort as well as the type of graft used. 4 , 5 When performing anterior cruciate ligament reconstruction (ACLR) in a growing adolescent athlete, the common graft options include hamstring tendon autograft versus quadriceps tendon autograft. The hamstring tendon autograft is more frequently used in the skeletally immature adolescent population, but recent investigations have focused on the quadriceps tendon as a potential superior alternative.…”
mentioning
confidence: 99%